Destination social capital and innovation in SMEs tourism firms: an empirical analysis in an adverse socio-economic context - Rastrollo-Horrillo, María Ángeles; Rivero Díaz, Mayra (Taylor & Francis, 2019)
This study examines the structural relationships between internal and external resources that explain the innovation of small tourism firms in adverse socio-economic contexts. Specifically, it analyzes two internal resources, human and organizational-technological capital, and the valuable intangible resources derived from social interactions between the agents in the destination (other companies, institutions, and community). The research hypotheses are tested by means of structural equation analysis applied to an empirical study of 180 tourism firms located in Isla Margarita (Venezuela). The findings confirm the importance of external resources derived from relationships with destination agents in the innovation behavior of tourism small and medium-sized enterprises (SMEs). While business social capital affects innovative behavior directly, other types of internal intellectual capital mediate the relationship between innovative behavior and institutional and community social capital. It is the first to address the local community’s role in the innovation of tourism SMEs. The importance of integrating firm and destination resources should inform SMEs’ innovation policies in adverse contexts where the scarcity of resources make vulnerable the economic, social and environmental sustainability.
https://openpolicyfinder.jisc.ac.uk/id/publication/19870?from=single_hit
Keywords: Turismo; Pequeñas y medianas empresas; Empresas turísticas - Innovaciones tecnológicas; Innovation; Social capital; Intellectual capital; Tourism SMEs; Tourism destination; Adverse context